Effectiveness of Control of Deep Agricultural Soil on Enrollment Perspective - Hasmawati Halim (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The objectives of this study were to: 1) Know why control over control of agricultural land has not been effective, 2) to know how to control of agricultural land through land registration. The data used in this study are primary data and secondary data that can support the assessment, which is then analyzed using qualitative methods with descriptive purposes. Based on the results of data analysis, it is concluded that: 1) Control of control over agricultural land in the perspective of land registration is less effective, this is due to conflicts of interest between the government, economic demands and a lack of understanding by the community that the importance of agricultural land for food security, which results in many agricultural lands being converted to non-agricultural land. In this case, BPN/ATR could not do much because of the constraints on land conversion permits issued by the local government. 2) Dominant factors causing Government Regulation Number. 24 of 1997 concerning Land Registration from a juridical perspective that there is no regulation regarding sanctions if land owners do not register their land. So that government supervision through BPN/ATR in the context of controlling control of agricultural land becomes less effective.